2023
DOI: 10.4244/eij-d-22-00070
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter interventions for heart failure

Abstract: Despite significant advances in the medical management of patients living with heart failure, there continues to be significant morbidity and mortality associated with the condition. There is a growing need for research and development of additional modalities to fill the management and treatment gaps, reduce hospitalisations and improve the quality of life for patients living with heart failure. In the last decade, there has been a rapid rise in the use of non-valvular catheter-based therapies for the managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…SIRONA was a first‐in‐human multicentre clinical study combining the commercially available Cordella Heart Failure System and the investigational Cordella Sensor to provide pulmonary artery pressure, weight, blood pressure, heart rate and oxygen saturations to patients and physicians through a remote monitoring system in ambulatory symptomatic HF patients (NYHA class III). The study showed that implantation of the Cordella Sensor was feasible and safe with excellent accuracy of the Cordella Sensor pulmonary artery pressure measurements, compared to fluid‐filled catheter at 3‐month follow‐up 96,97 . Patients that could benefit from haemodynamic monitoring system implantation are those with NYHA class ≥III, with an increased risk of WHF events or with a recent episode of WHF, displaying high pulmonary artery pressure at baseline.…”
Section: Early Detectionmentioning
confidence: 98%
See 1 more Smart Citation
“…SIRONA was a first‐in‐human multicentre clinical study combining the commercially available Cordella Heart Failure System and the investigational Cordella Sensor to provide pulmonary artery pressure, weight, blood pressure, heart rate and oxygen saturations to patients and physicians through a remote monitoring system in ambulatory symptomatic HF patients (NYHA class III). The study showed that implantation of the Cordella Sensor was feasible and safe with excellent accuracy of the Cordella Sensor pulmonary artery pressure measurements, compared to fluid‐filled catheter at 3‐month follow‐up 96,97 . Patients that could benefit from haemodynamic monitoring system implantation are those with NYHA class ≥III, with an increased risk of WHF events or with a recent episode of WHF, displaying high pulmonary artery pressure at baseline.…”
Section: Early Detectionmentioning
confidence: 98%
“…The study showed that implantation of the Cordella Sensor was feasible and safe with excellent accuracy of the Cordella Sensor pulmonary artery pressure measurements, compared to fluid-filled catheter at 3-month follow-up. 96,97 Patients that could benefit from haemodynamic monitoring system implantation are those with NYHA class ≥III, with an increased risk of WHF events or with a recent episode of WHF, displaying high pulmonary artery pressure at baseline. Cardiac resynchronization therapy and the implantable cardioverter-defibrillator offer diagnostic features that allow monitoring of several variables, including intrathoracic impedance used to measure changes in thoracic fluid content, intracardiac pressures, heart rate variability, patients' physical activity level, and arrhythmias.…”
Section: Devicesmentioning
confidence: 99%
“…Although existing therapies such as betablockers, angiotensin receptor-neprilysin inhibitors, and implantable cardiac defibrillators (ICD) have improved clinical outcomes, the need for more advanced treatment modalities is pressing [1]. Recently, catheter-based devices have emerged as promising interventions, targeting key pathophysiological mechanisms in HF progression [2]. The editorial highlights the potential of these novel devices in managing HF patients and the challenges ahead.…”
Section: Editorialmentioning
confidence: 99%
“…Given the lower intraprocedural risk compared to cardiac surgery, these approaches allowed us to treat a lot of patients previously judged ineligible. To date, TPs have revolutionized the treatment of the most common heart diseases, such as ischemic heart diseases, valvopathies, heart failure (HF), and arrhythmias, leading to improved life expectancy, QoL, and functional status [ 1 , 2 , 3 , 4 ]. A number of transcatheter interventions are performed in both Catheterization labs (Cath labs) and Electrophysiology labs (EP labs) today.…”
Section: Introductionmentioning
confidence: 99%